2023
DOI: 10.62335/nmgk6663
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Discipline and TPP on Performance Through Achievement Motivation in Civil Servants at The DPRD Secretariat Purwakarta District

Dinda Amalia,
Eti Jumiati,
Intan Rusita Ningrum

Abstract: This study aims to analyze the effect of discipline and additional employee income (TPP) on performance through achievement motivation as an intervening variable in the State Civil Apparatus at the Purwakarta Regency DPRD secretariat. The data source in this study was obtained from a questionnaire (primary) distributed to respondents. The population of this research is the staff of DPRD Purwakarta. The research sample amounted to 24 people. The research analysis method used is the outer model and inner model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Prior research has shown that teachers' performance is significantly influenced by principal leadership and teacher motivation in completing tasks (Firlianza & Suhardi, 2024;Mukhtar et al, 2024). The following section presents prior research on achievement motivation conducted by Amalia et al (2023), Li et al (2022), andYunus et al (2021). College students' employability is still significantly and positively influenced by achievement motivation This research presents novelty research that combines the variables of achievement motivation, academic supervision, principal leadership, and teacher performance into a single research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that teachers' performance is significantly influenced by principal leadership and teacher motivation in completing tasks (Firlianza & Suhardi, 2024;Mukhtar et al, 2024). The following section presents prior research on achievement motivation conducted by Amalia et al (2023), Li et al (2022), andYunus et al (2021). College students' employability is still significantly and positively influenced by achievement motivation This research presents novelty research that combines the variables of achievement motivation, academic supervision, principal leadership, and teacher performance into a single research topic.…”
Section: Introductionmentioning
confidence: 99%